Negotiating liminality following life transitions: reflexive bricolage and liminal hotspots. (3rd December 2020) - Kerrane, Katy; Lindridge, Andrew; Dibb, Sally
Abstract : Purpose: This paper aims to investigate how consumption linked with life transitions can differ in its potential to bring about ongoing liminality. By examining how consumers can draw on overlapping systems of resources, different ways in which consumers negotiate ongoing liminality following the transition to motherhood are identified. Design/methodology/approach: The authors conducted an interpretive, exploratory study using in-depth phenomenological interviews with 23 South Asian mothers living in the UK. The sample consisted of mothers at different stages of motherhood. Findings: Following life transitions, consumers may encounter liminal hotspots at the intersection of overlapping systems of resources. The findings examine two liminal hotspots with differing potential to produce ongoing liminality. The study shows how consumers navigate these liminal hotspots in different ways, by accepting, rejecting and amalgamating the resources at hand. Research limitations/implications: The research sample could have been more diverse; future research could examine liminal hotspots relating to different minority groups and life transitions. Practical implications: Marketers need to examine the different ways in which consumers draw on different systems of resources following life transitions. The paper includes implications for how marketers segment, target and market to ethnic minority consumers. Originality/value: Due to increasingly fluid social conditions, there are likely to be growing numbers of consumers who experience ongoing liminality following life transitions. A preliminary framework is presented outlining different ways that consumers negotiate ongoing liminality by drawing on overlapping systems of resources, broadening the understanding of the role that marketplace resources play beyond life transitions.